2000
DOI: 10.2746/042516400777584640
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative documentation of the racing performance of 461 Thoroughbred racehorses after arthroscopic removal of dorsoproximal first phalanx osteochondral fractures (1986–1995)

Abstract: Summary The purpose of this study was to examine the longevity of postoperative careers and quality of performance of 461 Thoroughbred racehorses after arthroscopic removal of dorsoproximal first phalanx (P1) osteochondral fractures. Six hundred and 59 dorsoproximal P1 chip fractures were removed arthroscopically from 574 joints in 461 horses presented forlameness or decreased performance attributed to the chip fractures. Radiological and arthroscopic examination revealed an average of 1.43 fragment sites/hors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 3 publications
12
76
2
Order By: Relevance
“…The average earnings per start after surgery was less than the average earnings before surgery in 61% of these horses and greater in 32%. This paper confirmed that the quantity and quality of performance was not diminished after arthroscopic treatment of dorsoproximal fragments, and that surgical removal of a chip fragment preserved the economic value of a racing Thoroughbred, allowing a rapid and successful return to racing at the previous level of performance (Colon et al, 2000). Colon et al (2000) considered the 11% postoperative failure rate to be due to various factors.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The average earnings per start after surgery was less than the average earnings before surgery in 61% of these horses and greater in 32%. This paper confirmed that the quantity and quality of performance was not diminished after arthroscopic treatment of dorsoproximal fragments, and that surgical removal of a chip fragment preserved the economic value of a racing Thoroughbred, allowing a rapid and successful return to racing at the previous level of performance (Colon et al, 2000). Colon et al (2000) considered the 11% postoperative failure rate to be due to various factors.…”
Section: Resultssupporting
confidence: 61%
“…In a third study done to examine the longevity of postoperative careers and quality of performance of 461 Thoroughbred racehorses after arthroscopic removal of dorsoproximal osteochondral fragments from the proximal phalanx, 659 chip fragments were removed from 574 joints (Colon et al, 2000). It was found that 89% of the horses (411/461) raced after surgery and 82% (377/461) did so at the same or a higher class; 68% of the horses raced in a stakes or allowance race postoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…However, appropriate facilities and personnel to handle horses are required, and the cost, although similar to canine models, is greater than for laboratory animals. Although we were not able to follow these horses out to 12 – 24 months after fragment removal to determine their long-term health, previous clinical studies where similar naturally-occurring OC fragments have been removed in equine athletes have shown a high percentage of return to use 13–15 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, creation of an OC fragment in the MCP joint may serve as a useful model in the study of PTOA. Furthermore, because removal of OC fragments in clinical cases will often result in a high percentage of return to racing 14, 15 , it is conceivable that the model can be non-terminal by removing the OC fragment at the end of the study period. Creation of an OC injury in the equine carpal joint has been used as an OA model to test various therapeutics 16, 17 , showing translational benefit to humans 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal impulsive loading was reported to induce high bone remodeling, microdamage and vascular invasion in subchondral bone, which eventually reduced its elasticity and led to subchondral bone sclerosis [9,67,68]. Racehorses running long distances at high speeds exhibited tremendous changes within the subchondral bone in the carpal and metacarpophalangeal joints, including osteochondral fragmentation and fracture, subchondral bone necrosis and sclerosis [69,70]. …”
Section: Factors Affecting Subchondral Bone Integritymentioning
confidence: 99%